Pioneer translation products as an alternative source for MHC-I antigenic peptides - Apcher, Sebastien; Daskalogianni, Chrysoula; Fåhraeus, Robin (Molecular immunology, 2015)
The notion that alternative peptide substrates can be processed and presented to the MHC class I pathway has opened for new aspects on how the immune system detects infected or damaged cells. Recent works show that antigenic peptides are derived from intron sequences in pre-mRNAs target for the nonsense-mediated degradation pathway. Introns are spliced out co-transcriptionally suggesting that such pioneer translation products (PTPs) are synthesized on the nascent RNAs in the nuclear compartment to ensure that the first peptides to emerge from an mRNA are destined for the class I pathway. This illustrates an independent translation event during mRNA maturation that give rise to specific peptide products with a specific function in the immune system. The characterization of the translation apparatus responsible for PTP synthesis will pave the way for understanding how PTP production is regulated in different tissues under different conditions and will help designing new vaccine strategies.
Keywords: introny; Histocompatibility Antigens Class I; cytosol; RNA Splicing; Humans; lidé; peptidy; Peptides; Proteasome Endopeptidase Complex; proteosyntéza; proteasomový endopeptidasový komplex; CD8-Positive T-Lymphocytes; Dendritic Cells; RNA Precursors; prekurzory RNA; Protein Biosynthesis; dendritické buňky; prezentace antigenu; Introns; Cytosol; sestřih RNA; Antigen Presentation; Phagosomes; CD8-pozitivní T-lymfocyty; MHC antigeny I. třídy; Cell Nucleus; fagozomy; buněčné jádro